Determination of the volume air exchange in the apartment - Kapalo, P.; Domnita, F.; Bacotiu, C.; Voznyak, O. (Видавництво Львівської політехніки, 2016)
Currently in the building industry is trend to build buildings consuming little energy. For the aim reducing heat loss buildings they are building insulated and also air tightness of buildings increases.. By improving the air tightness of buildings, there is a change of indoor air quality in buildings. Without natural or mechanical of ventilation there is a significant deterioration of indoor air quality. For the raising of quality indoor air is optimal system with demand-controlled ventilation using sensing of carbon dioxide. From sensing of carbon dioxide is possibly calculated mass flow of carbon dioxide for various type of rooms and various activity in them. In article is documented the calculation of mass flow of carbon dioxide for various activity in the apartment. The calculation is elaborated as per real measured of carbon dioxide in the apartment. From the calculated mass flow is calculated volume air flow necessary for provision fresh air in the apartment. The aim of the paper is to determine the needed airflow rate in an occupied room, based on carbon dioxide measurement. Accordingly is calculation, in order to maintain a comfortable level of indoor air quality. The calculated airflow rate should optimize the investment and the operating costs of ventilation equipment. Controlled Ventilation has to offer new technical tools for the indoor air quality of complex buildings. Our aim is not only improve the energy efficiency of the ventilation system, but also to ensure a healthy indoor environment. Сьогодні у будівельній галузі є тенденція будувати будівлі, які споживають мало енергії. Для зниження тепловтрат будівелі теплоізолюються, а також збільшується герметичність будівель. Внаслідок поліпшення повітронепроникності будівель відбувається зміна якості повітря всередині приміщень. Без природної або механічної вентиляції спостерігається значне погіршення якості повітря у приміщенні. Для підвищення якості повітря в приміщенні використовують систему примусової механічної вентиляції за допомогою зондування вуглекислого газу. Завдяки цьому явищу є можливість обчислення масової витрати вуглекислого газу для різної інтенсивності роботи у приміщенні. Описано обчислення масової витрати вуглекислого газу для різної активності роботи у квартирі. Розрахунок зроблено відповідно до реально виміряної кількості вуглекислого газу в квартирі. За розрахованою масовою витратою визначають необхідну кількість свіжого повітря у квартирі. Метою роботи є визначення необхідної витрати повітря у приміщенні на основі вимірювання вмісту вуглекислого газу. Відповідно до обчислення підтримується комфортний рівень якості повітря у приміщенні. Розрахункова витрата повітря повинна оптимізувати капітальні та експлуатаційні витрати вентиляційного обладнання. Організована вентиляція може запропонувати нові технічні засоби для якості повітря в приміщеннях комплексних будівель. Наша мета не тільки поліпшити енергетичну ефективність системи вентиляції, а й забезпечити сприятливе для здоров’я внутрішнє повітряне середовище.
Keywords: indoor air quality; carbon dioxide; mass flow; apartment; якість внутрішнього повітря; двоокис вуглецю; масова витрата; квартира